Design and development of optical biosensors coupling gold nanoparticles or silver nanoclusters with hybridisation chain reaction - Ooi, Jessica Sui Ying (2025)
Optical biosensors play a crucial role in detecting specific analytes, including nucleic acids, proteins, metabolites and metal ions. Label-free optical biosensors utilising noble metal nanoparticles have the potential to revolutionise detection of cancer due to their high selectivity, sensitivity, and rapid results.